Suggestions for the revision and implementation of the dermatopathology teaching syllabus - LIU Hongjie; WANG Junlin; LI Wei; WANG Lin; YANG Xiao; ZHANG Xingwei; WEN Xiang; JIANG Xian; YAN Wei (Pifu-xingbing zhenliaoxue zazhi)
The dermatopathology teaching syllabus serves as a crucial foundation for conducting educational activities, and strict adherence to its requirements is essential for maintaining teaching quality. A well-designed syllabus is vital for improving training standards. After analyzing the evolution of two versions of the syllabus, we propose its revision and implementation based on clinical teaching practice. These include ①adjusting the required disease categories to incorporate livedoid vasculopathy, mycosis fungoides, and leprosy, replacing insect bite dermatitis, erythema multiforme, and melanosis, with justifications for these changes; ②incorporating direct immunofluorescence into the teaching requirements;③specifying the necessary types of special stains and immunohistochemical markers; ④emphasizing equal importance on image-based assessments and descriptive pathology assessments. Strategies for curriculum implementation include ①identifying key challenges, such as the uneven distribution of teaching faculty, insufficient foundational knowledge among resident physicians, and the absence of a continuous dermatopathology teaching framework; ②Corresponding measures include establishing regional collaborative training mechanisms for dermatopathology, employing a gross pattern teaching approach in slide review sessions, organizing a dermatopathology competition for resident physicians and conducting weekly dermatopathology group meetings to study recent representative cases.